The influence of the Arguedas’ tale in the development of the work ‘El Ayla’ of Nilo Velarde - Berrospi Gutiérrez, Diego Ivan (2022)
Throughout the history of universal academic composition there has been a constant motivation of creators to explore elements, musical or not, that can generate a feature of national, regional, or personal identity. This, of course, has not been alien to the Peruvian musical reality, finding a kind of symbiosis with other cultural branches, and being an alternative for the writing of new music from the late twentieth century to present. To this end, this work is based on the analysis to determine those musical elements that show an artistic influence of the story “El Ayla,” by José María Arguedas, in the creative process of the composer Nilo Velarde Chong, who is one the most prominent Peruvian musicians of the new century, for the elaboration of his homonymous work, composed for chamber ensemble.